Analisis Tingkat Kepuasan Wisatawan Terhadap Pelayanan Pemandu Wisata di PT. Pacto Tour Travel and Mice Medan - Yosi Septrix Sipayung; Merry Moy Mita; Angelia Putriana (TOBA: Journal of Tourism, Hospitality, and Destination, 2022)
This study aims to determine the level of tourist satisfaction in using the services of a large tour guide by PT. Pacto Tour Travel and MICE Medan. This study uses qualitative research, data collection techniques of observation, interviews, and documentation. The population of this study collected 250 respondents and took samples using a purpose sampling technique, because the sampling of population members was carried out by utilizing tourists who were on vacation in the tourist attraction area of 25 tourists. The data analysis technique used is data reduction, data presentation and leveraging conclusions. The results showed that the services provided by PT. Pacto Tour Travel and MICE In this study, namely tangible evidence (Tangibles), Reliability, Assurance, Responsiveness, Empathy, and satisfaction can be felt very comfortable by tourists in using the services of PT. Pacto Tour Travel and MICE Medan. The comfort felt by tourists is good because tourist guides can provide a positive response for tourists who come to North Sumatra both locally and abroad and are also quite friendly tour guides.